Structure and dynamics of livelihoods in rural India: A panel data analysis. Issue 3 (31st August 2022) - Dey, Sagarika
Abstract: The paper uses panel data from two rounds of the Indian Human Development Survey (IHDS) to evaluate the trends in rural livelihoods in India during 2005–2012. Although the macrostructure of rural livelihoods did not seem to change during the period under consideration, livelihoods remained in a state of flux with about 57% of the households changing their livelihood strategy at least once between 2005 and 2012. Most of these transitions occurred from one low‐paying strategy to another. There was also an increasing trend towards marginalisation of labor which is evident from the fact that cultivation, which was the most widely pursued strategy in 2005, was relegated to the second spot while casual wage‐based labor emerged as the most dominant livelihood strategy in 2012. Household assets played a predominant role in influencing both the current choice of livelihoods and in determining livelihood transitions. Education and financial inclusion were found to be extremely potent in aiding households in moving out from low‐paying strategies, and also in preventing a downward slide along the livelihood curve. Significant variations in livelihood conditions were observed across states with households in Western and Southern India adopting more vulnerable strategies. Resumen: El documento utiliza datos de panel de dos rondas de la Encuesta de Desarrollo Humano de India (IHDS) para evaluar las tendencias en los medios de vida rurales en India durante 2005‐2012. Aunque la estructura macro de los medios de vida rurales no pareció cambiar durante el período bajo consideración, los medios de vida permanecieron en un estado de cambio constante con alrededor del 57 por ciento de los hogares cambiando su estrategia de medios de vida al menos una vez entre 2005 y 2012. La mayoría de estas transiciones ocurrieron de una estrategia de pago bajo a otra. También hubo una tendencia creciente hacia la marginación del trabajo, lo que es evidente por el hecho de que el cultivo, que era la estrategia más seguida en 2005, quedó relegado al segundo lugar y el trabajo asalariado ocasional surgió como la estrategia de subsistencia más dominante en 2012. Activos domésticos desempeñó un papel predominante al influir tanto en la elección actual de los medios de vida como en la determinación de las transiciones de los medios de vida. Se encontró que la educación y la inclusión financiera son extremadamente potentes para ayudar a los hogares a salir de las estrategias de bajos salarios y también para prevenir una caída a lo largo de la curva de medios de vida. Se observaron variaciones significativas en las condiciones de subsistencia en todos los estados con hogares en el oeste y el sur de la India que adoptaron estrategias más vulnerables. 摘要: 本文使用两轮印度人类发展调查(IHDS)的面板数据来评估2005‐2012年印度农村生计的趋势。虽然农村生计的宏观结构在所考察的期间似乎没有改变，但生计仍处于不断变化的状态——大约57%的家庭在2005‐2012年间至少改变了一次生计策略。这些变化大部分是从一种低薪策略转变到另一种。劳动边缘化也出现上升趋势，这从2005年最广泛推行的种植策略退居第二位，2012年以临时工资为基础的劳动成为最主要的生计策略这一事实就可以看出。家庭资产在影响当前的生计选择和决定生计转变方面发挥了主要作用。教育和金融包容性被发现在帮助家庭摆脱低收入战略以及防止生计曲线下滑方面非常有效。各邦的生计条件存在显著差异，其中印度西部和南部的家庭采用了更脆弱的策略。